Heat transfer and smoke flow filling progress in a super-high atrium under influence of fire source characteristics. (May 2019) - Chen, Yanqiu; Wang, Dong; Chen, Junmin
Heat transfer and smoke flow filling progress in a super-high atrium is studied in this article. The influences of heat release rate and fire source height were considered. It was found that the fire smoke layer could not reach the top of the atrium when the heat release rate was very low and the fire source was located at the bottom of the atrium. The temperature of smoke layer interface and Δ T max were linearly positively related to Q 2/3, while Δ P max was quadratically positively related to Q 2/3 . At the top of the atrium, the temperature rise and fire source height were consistent with the Boltzmann model. As the fire smoke rose with a velocity, a relatively low-pressure area was generated below. The pressure variation in this area was negatively index-related to the fire source height.